The limits of blame rethinking punishment and responsibility - Kelly, Erin 1976- (Harvard University Press, 2018)
Faith in the power and righteousness of retribution has taken over the American criminal justice system. Approaching punishment and responsibility from a philosophical perspective, Limits of Blame takes issue with a criminal justice system that aligns legal criteria of guilt with moral criteria of blameworthiness. Many incarcerated people do not meet the criteria of blameworthiness, even when they are guilty of crimes. The author underscores the problems of exaggerating what criminal guilt indicates, particularly when it is tied to the illusion that we know how long and in what ways criminals should suffer. Our practice of assigning blame has gone beyond a pragmatic need for protection and a moral need to repudiate harmful acts publicly. It represents a desire for retribution that normalizes excessive punishment. Kelly proposes that we abandon our culture of blame and aim at reducing serious crime rather than imposing retribution. Were we to refocus our perspective to fit the relevant moral circumstances and legal criteria, we could endorse a humane, appropriately limited, and more productive approach to criminal justice....
Keywords: Retribution -- Philosophy; Punishment -- United States -- Philosophy; Criminal liability -- United States -- Philosophy; Strafe; Rechtssystem; Verantwortung; Philosophie